2023
DOI: 10.1177/23337214231186204
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Loneliness and Isolation in Older Adults With Virtual Reality: How do We Move Forward?

Abstract: Current trends in gerontology conceptualize Virtual Reality (VR) as a tool for rehabilitation, lauding its potential for cognitive rehabilitation or as an intervention to reduce cognitive function decline. However, we must take a critical stance and identify not just the potential positive impact, but also how things may go wrong without appropriate guidelines, and the need for careful design around the interaction affordances of the technology. We conducted co-discovery and co-design workshops involving exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Given that loneliness is a very important issue amongst older populations and many adults fear becoming lonely (Cohen-Mans eld et al, 2016), perceiving a technology as potentially fostering loneliness will face di culty in its adoption by end users. Indeed, other studies investigating VR in connection to loneliness have found the same issue between fostering and remedying loneliness (Finnegan & Campbell, 2023;Healy et al, 2022;Restout et al, 2023). Finnegan & Campbell (2023) suggest designing and using VR in a more nuanced way based on emotion rather than a label, thus not framing it as a technology for lonely persons, but persons who feel lonely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that loneliness is a very important issue amongst older populations and many adults fear becoming lonely (Cohen-Mans eld et al, 2016), perceiving a technology as potentially fostering loneliness will face di culty in its adoption by end users. Indeed, other studies investigating VR in connection to loneliness have found the same issue between fostering and remedying loneliness (Finnegan & Campbell, 2023;Healy et al, 2022;Restout et al, 2023). Finnegan & Campbell (2023) suggest designing and using VR in a more nuanced way based on emotion rather than a label, thus not framing it as a technology for lonely persons, but persons who feel lonely.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other studies investigating VR in connection to loneliness have found the same issue between fostering and remedying loneliness (Finnegan & Campbell, 2023;Healy et al, 2022;Restout et al, 2023). Finnegan & Campbell (2023) suggest designing and using VR in a more nuanced way based on emotion rather than a label, thus not framing it as a technology for lonely persons, but persons who feel lonely. Older adults could therefore be encouraged to take activities that they used to enjoy to a virtual level in order to socialize and combat feelings of loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…As the elderly population was particularly effected by quarantine measures enforced during the lockdown worldwide, resulting in a significant reduction of occasions for social interactions [29], different attempts of engaging them through social VR platforms over that period were performed. Finnegan et al designed several VR prototypes in VRChat and prototyped them with elderly people, demonstrating that the space and the activities performed in VR do matter when tackling loneliness and isolation in elderly people [30]. Their research pointed out that social VR research has so far focusing on passive consumption of content on reliving the past, while their findings suggest that supporting the formation of groups around new activities to perform together could be key in the design of VR experiences for elderly people.…”
Section: Immersive Experiences Against Social Isolationmentioning
confidence: 99%